MENINGKATKAN HASIL BELAJAR SISWA PADA MATA PELAJARAN ILMU PENGETAHUAN SOSIAL (IPS) MELALUI PENERAPAN MEDIA VISUAL PADA SISWA KELAS VIII-2 SMP NEGERI 1 STM HULU TAHUN PELAJARAN 2019/2020 - Erika Asnidar Br. Singarimbun (ANSIRU PAI : Pengembangan Profesi Guru Pendidikan Agama Islam, 2020)
Classroom Action Research The location of this research was carried out at SMP Negeri 1 STM Hulu. The research was conducted in September 2019 to November 2019. The subjects of this study were students of class VIII-2 SMP Negeri 1 STM Hulu Academic Year 2019/2020 with a total of 34 students. Which consists of 19 men and 15 women. Learning outcomes are benchmarks used to determine the level of student success in knowing and understanding a subject, usually expressed by values in the form of letters or numbers. Media is one of the determining factors for the success of learning. In addition, the media also helps clarify learning messages. The successful use of media cannot be separated from how well the media is planned. The results of Cycle I and 34 students who were the subjects in this study turned out that there were 20 students (58.82%) who had active learning, while 14 students (41.18%) still did not have active learning. The class average value obtained in this cycle reached 64.18. Whereas in cycle II it can be seen that the students' ability to test classical learning outcomes has increased. It turned out that and 34 students, there were 32 active students (94.11%) who already had active learning, while the rest, 2 students (5.89%), did not have active learning. The average value obtained only reaches 82.1. The conclusion of this classroom action research is "There is an increase in student learning outcomes in social science subjects through the application of visual media to class VIII-2 students of SMP Negeri 1 STM Hulu.